Long‐term veno‐arterial extracorporeal membrane oxygenation as a bridge to heart–lung transplant. Issue 3 (27th January 2021) - Trezzi, Matteo; Brancaccio, Gianluca; Giorni, Chiara; Ricci, Zaccaria; Iacobelli, Roberta; di Chiara, Luca; Amodeo, Antonio
Abstract: En bloc heart–lung transplantation still represents definitive therapy for end‐stage cardiopulmonary failure. However, patients may critically decompensate while awaiting suitable donor organs and necessitate veno‐arterial extracorporeal membrane oxygenation. In this article, we describe the combined use of central cannulation with the Berlin Heart EXCOR ventricular assist device cannulae and the CentriMag centrifugal pump as an extended bridge to heart–lung transplantation in three pediatric patients.